The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/rec.13525
|View full text |Cite
|
Sign up to set email alerts
|

Feed the bees and shade the streams: riparian shrubs planted for restoration provide forage for native bees

Abstract: With evidence of pollinator declines and an increasing focus on restoration, interest is growing in investigating floral resources for native bees. Although native bees forage on shrubs, few studies have explored the pollinator communities of native shrubs and none have examined shrub-pollinator interactions in riparian areas of the northwestern United States. Life history traits of shrubs may make them particularly important resources for bees, especially in early spring-a key point in the lifecycle of many b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…It has been previously suggested that planting willows near fruit and berry crops is an effective way to increase fruit production via increased pollination [14,51]. Both native and introduced willows may be strategically planted near agricultural fields along with pollinator-dependent crops to provide essential nutrient resources for bees prior to the mass flowering of agricultural crops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously suggested that planting willows near fruit and berry crops is an effective way to increase fruit production via increased pollination [14,51]. Both native and introduced willows may be strategically planted near agricultural fields along with pollinator-dependent crops to provide essential nutrient resources for bees prior to the mass flowering of agricultural crops.…”
Section: Discussionmentioning
confidence: 99%
“…For example, willows support a high density of breeding bird communities by providing services such as nesting, food, and stopover sites [13]. Willows are considered an ecosystem "foundation species", due to the high number of insects they bolster [14]. Furthermore, willow short rotation coppice (SRC) plantations reduce the negative consequences of habitat fragmentation with the provision of food and shelter for a high proportion of animals that move from adjacent habitats into the plantations [15].…”
Section: Introductionmentioning
confidence: 99%
“…Data from all five transects were combined, creating a single dataset for each site. As in other pollinator studies (e.g., Roof et al, 2018 ;Graham et al 2021 ;Mitchell et al 2021 ), we defined blooming stems as individual flowers or clusters of flowers arranged on a stem.…”
Section: Plant Community Samplingmentioning
confidence: 99%
“…(Rood et al 2003;Golet et al 2011). The faunal diversity can indicate the success of riparian ecosystem restoration (Golet et al 2008 and2011;Gollan et al 2011;Wortley et al 2013;Mitchell et al 2021); however, a few studies have shown that not all species can be taken into account. For example, using prey availability was not successful in the evaluation of the restoration programme at lower Colorado River (Rubin et al 2019).…”
Section: Assessment Of Riparian Restorationmentioning
confidence: 99%